2021
DOI: 10.1364/boe.425512
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and quantification of necrotic tissues and morphology in multicellular ovarian cancer tumor spheroids using optical coherence tomography

Abstract: The three-dimensional (3D) tumor spheroid model is a critical tool for high-throughput ovarian cancer research and anticancer drug development in vitro. However, the 3D structure prevents high-resolution imaging of the inner side of the spheroids. We aim to visualize and characterize 3D morphological and physiological information of the contact multicellular ovarian tumor spheroids growing over time. We intend to further evaluate the distinctive evolutions of the tumor spheroid and necrotic tissue volumes in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Drug resistance is often associated with the formation of a hypoxic core (necrotic core) 38 . Therefore, we aimed to form large spheroids (>500 μm in diameter) since those larger than 500 μm in diameter exhibit gradient and zone formation 39,40 . In this study, we cultivated and analyzed spheroid growth, utilizing them on day 7 post-formation when they reached approximately 800 mm in diameter (Figure 2A and 2B) .…”
Section: Resultsmentioning
confidence: 99%
“…Drug resistance is often associated with the formation of a hypoxic core (necrotic core) 38 . Therefore, we aimed to form large spheroids (>500 μm in diameter) since those larger than 500 μm in diameter exhibit gradient and zone formation 39,40 . In this study, we cultivated and analyzed spheroid growth, utilizing them on day 7 post-formation when they reached approximately 800 mm in diameter (Figure 2A and 2B) .…”
Section: Resultsmentioning
confidence: 99%
“…A swept-source OCT imaging system (VEG220, Thorlabs) with a swept-source laser of 1310 nm center wavelength and 100 nm spectral bandwidth was employed to provide an axial resolution of 14 μm in the air (10 μm in mouse brain) and lateral resolution of 20 μm. The wavelengthswept frequency and sensitivity in this system were 200 kHz and 98 dB, respectively [27][28][29][30][31][32][33][34][35][36][37]. The OCT-based optical microangiography (OMAG) algorithm was utilized to acquire in vivo volumetric angiography in mouse cerebral cortex by coherently analyzing the intrinsic scattering property of moving red blood cells (RBCs) in blood vessels [15,25].…”
Section: Optical Coherence Tomography Angiographymentioning
confidence: 99%
“…This study demonstrated the spheroid imaging of hypoxia that could be a future target for the drug-screening analysis. In other cell lines, ovarian cancer cell (OVCAR-8) was applied to visualize 3D structures and monitor necrotic zones within the MCTs (Figure 7F) [146]. In this study, a swept-source optical coherence tomography platform was fabricated, and OCT images were obtained.…”
Section: Optical Coherence Tomography-based Biosensingmentioning
confidence: 99%
“…Copyright 2020, Wiley Online Library; Reprinted with permission from [121]. Copyright 2020, American Chemical Society; Reprinted with permission from [146]. Copyright 2021, Optical Society of America; Reprinted with permission from [110].…”
Section: Optical Coherence Tomography-based Biosensingmentioning
confidence: 99%